Keyakinan Hukum Karma Memoderasi Pengaruh Hedonisme Pada Kecurangan Dalam Pelaporan Keuangan - Megawati, Anak Agung Tri (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p06, 2022)
This study aims to examine the effect of hedonism on fraudulent financial reporting and the belief in the law of karma as a moderating variable of the effect of hedonism on fraud. This type of research is quantitative. The research was conducted at the Village Credit Institution in Denpasar City using primary data obtained by distributing questionnaires. The method of determining the sample using the saturated method and obtained as many as 105 respondents. The data analysis technique used is the interaction test of the moderating variable Moderated Regression Analysis (MRA). Based on the results of the analysis, it shows that hedonism has a negative effect on fraudulent financial reporting. The results of the study indicate that high hedonism in an individual can reduce the occurrence of fraud in financial reporting. The belief in the law of karma moderates the effect of hedonism on fraud that the belief in the law of karma weakens the influence of hedonism on fraud in financial reporting. Keywords: Hedonism; Belief in the Law of Karma; Financial Reporting Fraud .